2015
DOI: 10.3892/ol.2015.3863
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor exon 20 p.S768I mutation in non-small cell lung carcinoma: A case report combined with a review of the literature and investigation of clinical significance

Abstract: Abstract. Epidermal growth factor receptor (EGFR) plays a significant role in non-small cell lung cancer (NSCLC), the most prevalent form of lung cancer worldwide. Therefore, EGFR may be a useful molecular target for personalized therapy utilizing tyrosine kinase inhibitors (TKIs). Somatic activating EGFR mutations may be used to identify tumors sensitive to the effects of small-molecule EGFR-TKIs (gefitinib and erlotinib), and alternative, less frequently observed mutations, including the majority of mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
1
1
0
1
Order By: Relevance
“…From previous studies, a mutation in the EGFR at 2235_2249 delggaattaagagaagc (Del E746-A750) in exon 19 (Marchetti et al, 2005;Jorge et al, 2014) and a new insertion at 2313_2314insCAC position (771_772insHis) in exon 20 have been found. The database showed a correlation between the pattern from the PCR-SSCP and that from the control that was confirmed by DNA sequencing, which previous studies have not reported (Arcila et al, 2013;Improta et al, 2016;Zupa et al, 2012).…”
Section: Discussionsupporting
confidence: 69%
“…From previous studies, a mutation in the EGFR at 2235_2249 delggaattaagagaagc (Del E746-A750) in exon 19 (Marchetti et al, 2005;Jorge et al, 2014) and a new insertion at 2313_2314insCAC position (771_772insHis) in exon 20 have been found. The database showed a correlation between the pattern from the PCR-SSCP and that from the control that was confirmed by DNA sequencing, which previous studies have not reported (Arcila et al, 2013;Improta et al, 2016;Zupa et al, 2012).…”
Section: Discussionsupporting
confidence: 69%
“…p.S768I has been categorized as a primary resistant EGFR mutation[40], although there are conflicting opinions from other studies with small case numbers [41, 42]. The largest cohort study showed TKIs were less effective in 7 patients with p.S768I mutation [43].…”
Section: Discussionmentioning
confidence: 99%
“…Ekzon 20 üzerinde saptanan mutasyonlar genellikle tedaviye dirençli değişikliklerdir (5). Bu durumun istisnası ekzon 20 üzerinde pozisyon 768 ve öncesindeki insersiyonlardır (6,7). EGFR tirozin kinaz inhibitörleriyle tedavi olan hastaların çok büyük bir kısmında tedavinin bir noktasında ilaca karşı gelişen direnç nedeniyle relaps görülür.…”
Section: Egfr Mutasyonuunclassified